2006
DOI: 10.1007/bf03349204
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular acute and chronic administration of obestatin minimally affect food intake but not weight gain in the rat

Abstract: We studied the effect of the acute central administration of obestatin on food intake and body weight in short-term starved male rats, and those of 28-day continuous intracerebroventricular (icv) infusion of obestatin in free feeding rats. In 16-h starved rats, obestatin induced a trend toward a reduction of food intake that did not reach statistical significance. In fed rats, the icv infusion of obestatin significantly decreased food consumption in the first day of treatment; but the anorexigenic effect of ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 13 publications
0
22
0
2
Order By: Relevance
“…Similarly, Sibilia et al [6] found that low or moderate dosages of obestatin (0.75 and 1.2 microgram /rat) had no significant impact on body weight. Moreover, Taghian and Zolfaghari.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similarly, Sibilia et al [6] found that low or moderate dosages of obestatin (0.75 and 1.2 microgram /rat) had no significant impact on body weight. Moreover, Taghian and Zolfaghari.…”
Section: Discussionmentioning
confidence: 93%
“…As a case in point, Sibilia et al [6] found that obestatin had an appetitesuppressing impact and a significant role in weight loss. However, some other researchers observed that peripheral obestatin had no impact on appetite or food intake [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, obestatin is produced by the gastrointestinal tract, the peripheral obestatin might cross the bloodbrain barrier and enter the hippocampus and amygdala and by activating these brain regions they may modulate the behavior of rodents [13]. We administrated obestatin centrally in harmony with previous studies [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…All in all, data concerning obestatin's influence on feeding behavior when injected peripherally are conflicting. There are four studies describing a significant inhibitory effect on food intake [7,18,27,51], three investigations showing a non-significant trend towards a reduction [21,40,42], and seven reports of no effect on feeding behavior after obestatin administration [11,14,15,32,41,54, and present study]. The results of these studies seem to be independent from the investigated species (mice or rats), the metabolic status (fasted or fed ad libitum) and the route of delivery (ip, intravenous, intracerebroventricular and intracisternal) [16 and present study].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that obestatin may be involved in the regulation of energy homeostasis in rodents. However, several recent studies performed in rats and mice under various experimental conditions showed that obestatin injected intraperitoneally (ip) has no inhibitory effect on short-term food intake [11,[14][15][16][17]21,32,41,54] and body weight gain [32,42]. The responsiveness to exogenous obestatin could be influenced by circadian rhythm and might account for the varying effects of peripheral obestatin on food intake found in recent studies [7,15,18,21,27,32,[40][41][42]51,54].…”
Section: Introductionmentioning
confidence: 99%